Task-dependent audiovisual temporal sensitivity is not affected by stimulus intensity levels - Scurry, Alexandra N. (Vision Res, 2021)
Flexibility and robustness of multisensory temporal recalibration is paramount for maintaining perceptual constancy of the surrounding natural world. Different environments impart various impediments, distances and routes that alter the propagation times of sight and sound cues comprising a multimodal event. One’s ability to rapidly calibrate and account for these external variations allows for maintained perception of synchrony which is crucial for coherent and consistent perception. The two common paradigms used to compare precision of temporal processing between experimental and control groups, the simultaneity judgment (SJ) and temporal order judgment (TOJ) tasks, often use supra-threshold stimuli. However, few studies have specifically examined the effects of normalizing stimulus intensities to participant’s unisensory detection thresholds. The current project presented multiple combinations of auditory and visual stimulus intensity levels, based on individual detection thresholds, during a TOJ and a SJ task. While no effect of stimulus intensity was found on temporal sensitivity or perceived temporal synchrony, there was a significant difference in point of subjective simultaneity (PSS) measures between tasks. In addition, PSS estimates were audio-leading, rather than visual-leading as previously reported, suggesting that exposure to the particular combinations of stimulus intensity levels used influenced temporal synchrony perception. Overall, these results support the use of supra-threshold stimuli in TOJ and SJ tasks as a way of minimizing the confound from differences in unisensory processing.